Pengelolaan hasil tanaman obat keluarga (TOGA) jamu instan jahe merah (Zingiber officinale var. rubrum) - Rahmawati Raising; Novi Ayuwardani; Oktaviarika Dewi Hermawatiningsih; Yetti Hariningsih; Vevi Maritha; Tika Indrasari (INDRA: Jurnal Pengabdian kepada Masyarakat, 2023)
Community participation in health development with TOGA (Family Medicinal Plants) or commonly referred to as a live pharmacy, in order to meet the family's need for medicines. Cultivation of medicinal plants for families (TOGA) can stimulate small and medium enterprises in the field of herbal medicine. Red ginger is one of the herbal plants that has been widely known as a health support product by the public because empirically it has many health benefits such as anti-inflammatory, reducing nausea and immunomodulatory with few side effects. Therefore, training is needed to improve the skills of PKK team in making Red Ginger Instant herbal products, the target of this community service activity is PKK team, using presentation methods, demonstrations on how to make red ginger instant herbal products. The results of this community service activity increase understanding of making instant herbal medicine